Fragmentation issue in Malaysian Industrialised Building System (IBS) projects - Mohd Nawi Mohd Nasrun, Lee Angela, Azman Mohamed Nor Azhari, Mohamad Kamar Kamarul Anuar, (N/A, 2014)
Fragmentation issue in Malaysian Industrialised Building System (IBS) projects by Mohd Nawi Mohd Nasrun, Lee Angela, Azman Mohamed Nor Azhari, Mohamad Kamar Kamarul Anuar,